The Structural Analysis of The Main Character in Cinderella’s Short Story in Grimms Fairy Tales - Radharani, Sri (Journal of Linguistic and Literature Studies, 2023)
The purpose of this study is to analyze the structure of the two Cinderella's short stories, namely Cinderella in Grimm's Fairy Tales written by Jacob and Wilhelm Grimm, and by Jacob and Wilhelm Grimm edited by Edna Henry Lee Turpin. In order for the meaning of the story to be fully conveyed to the reader, it is necessary to present the relationship between the plot and other elements in the story, and structure has a very important role in presenting this. This analysis reveals the author's intention to compose a story through intrinsic elements, that is characters especially the main characters, which are then related to characterization. The results of this analysis are expected to help readers to broaden their understanding of the two Cinderella short stories through these elements.